2017
DOI: 10.1007/s00382-017-3591-3
|View full text |Cite
|
Sign up to set email alerts
|

How East Asian westerly jet’s meridional position affects the summer rainfall in Yangtze-Huaihe River Valley?

Abstract: negative); there is not much difference in these processes between early summer and midsummer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Many other studies have also confirmed that most extreme precipitation events over the NCP are concentrated in the period from mid‐July to mid‐August (Li & Wang, ). The 30‐day period from the second half of July to the first half of August is defined as midsummer over eastern China (Wang et al, ; Wang & Zuo, ). Thus, in this study, we define the period from 15 July to 15 August as midsummer to capture the most frequent period of extreme precipitation over the NCP.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have also confirmed that most extreme precipitation events over the NCP are concentrated in the period from mid‐July to mid‐August (Li & Wang, ). The 30‐day period from the second half of July to the first half of August is defined as midsummer over eastern China (Wang et al, ; Wang & Zuo, ). Thus, in this study, we define the period from 15 July to 15 August as midsummer to capture the most frequent period of extreme precipitation over the NCP.…”
Section: Introductionmentioning
confidence: 99%
“…During the warming period, the EAWJ shows a decreasing trend, which results in a stronger mixing of cold and warm air and leads to an increase in rainfall (Figure 5a). Studies also observed that the north and south displacement of the EAWJ also has an influence on the rainfall pattern [33][34][35]. During the hiatus period, the EAWJ moves northward, accompanied by anomalous convergence over the middle and high latitudes and anomalous divergence over the lower latitudes in the upper level, which results in increasing upward motion in the Huang-Huai River region and downward motion in the Yangtze River region and causes the rainfall belt to shift from the Yangtze River region to the Huang-Huai River region during this period ( Figure 5b).…”
Section: Variation In Summer Rainfall During the Warming And Hiatus Pmentioning
confidence: 99%
“…e upper-level westerly jet (WJ) is a planetary-scale atmospheric circulation system in the upper troposphere and is an important circulation system that affects the weather and climate in East Asia [18][19][20][21][22][23]. Hence, numerous researchers have studied the WJ [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%